Administration with hyperoside sensitizes breast cancer cells to paclitaxel by blocking the TLR4 signaling. (October 2020) - Sun, Ting; Liu, Yunyong; Li, Mengdan; Yu, Huihui; Piao, Haozhe
Abstract: Breast cancer is a malignancy and one of the most frequent causes of cancer death among women worldwide. Paclitaxel is a common chemotherapeutic drug and has recently been shown to facilitate tumor cell escape during cytotoxic chemotherapy by inducing inflammatory mediators and pro-survival protein expression. Hyperoside is a flavonoid glycoside compound and exerts anti-inflammation, and anti-tumor growth properties. However, its function in breast cancer chemosensitivity remains poorly elucidated. In this study, hyperoside exhibited little cytotoxicity to normal human breast mammary epithelial cell lines, and also protected against paclitaxel-induced cytotoxicity in MCF-10A. Importantly, treatment with hyperoside engendered not only inhibition of cell viability, but also potentiated cancer cell sensitivity to paclitaxel in TLR4-positive breast cancer MDA-MB-231 cells by suppressing cell viability, and increasing cell apoptosis and caspase-3 activity. Nevertheless, although hyperoside exposure restrained cell viability, its treatment presented little effects to paclitaxel sensitivity in TLR4-null HCC1806 cells. Intriguingly, paclitaxel stimulation activated the TLR4-NF-κB signaling, which was reversed after hyperoside administration. Concomitantly, hyperoside also attenuated paclitaxel-mediated anti-apoptotic Bcl-2 expression, but enhanced the effects of paclitaxel on pro-apoptotic Bax expression, and pro-inflammatory cytokine IL-6 and IL-6 levels in MDA-MB-231 cells. Importantly, restoring the TLR4 pathway overturned hyperoside-evoked chemosensitivity to paclitaxel in MDA-MB-231 cells. Thus, hyperoside may elevate breast cancer cell sensitivity to paclitaxel by blocking TLR4 activation-mediated pro-inflammatory and pro-survival approaches, thereby endorsing its usefulness as a promising therapeutic combination to overcome chemosensitivity in breast cancer. Graphical abstract: Image 1 Highlights: Hyperoside increases cell sensitivity to paclitaxel in TLR4-positive MDA-MB-231 cells. Hyperoside affords little efficacy on TLR4-null HCC1806 cell sensitivity to paclitaxel. Hyperoside mutes TLR4-NF-κB signaling in breast cancer cell response to paclitaxel. Hyperoside inhibits paclitaxel-induced apoptosis and inflammatory cytokine expression. Restoring TLR4 signaling offset hyperoside-mediated chemosesitivity to paclitaxel.